Makna ‘’Didiklah Orang Muda’’ menurut Amsal 22:6 dan Relevansinya bagi Gereja - Immanuelia Deru (Sekolah Tinggi Teologia Kerusso Indonesia, 2021)
Education is very vital to improve the quality of human resource. Therefore moral and spiritual education is very important for men in order to change the mindset, character, and increasing intelligence. Jesus startyed his ministry educating or teaching (Matthew 4:23). Every one who heard his teaching and believed him always experiences a change of attitude from bad to good (the apostles, Zaccheus, Samaritan woman). The Lord Jesus understood very well that education consists of very important teachings for one’s life. Teaching the Word of God contributed to the growth of the faith of the early church. It even contributed to the growth in quantity (Acts 2:41-42). The first and major Education agent here is the family. Parents are the main teacher for their children. Not only family, but then there is the church for the believers. As one of the assignments of the church is teaching (didache). The church has to teach or educate the people according to the Bible. Christian education needs to have the basic understanding that God is the source of knowledge or the Truth.3 The most important purpose of a Christian education is helping the students to know God through Jesus Christ, through His Word. To be able to achieve this, we need to have educators who deeply know God, through Jesus Christ and have experienced spiritual renewal.Keywords:; ;